Mangiferin content, carotenoids, tannins and oxygen radical absorbance capacity (ORAC) values of six mango (Mangifera indica) cultivars from the Colombian Caribbean (2017)
ABSTRACT: Mango is one of the tropical fruits of greater production and consumption in the world, and a rich source of bioactive compounds, with various functional properties such as antioxidant activity. In Colombia, mango’s market is very broad and diverse. However, there are very few studies that determined the content of bioactive secondary metabolites. The objective of this study was to evaluated the content of different metabolites like Mangiferin, carotenoids, tannins, and the antioxidant capacity by oxygen radical absorbance capacity (ORAC) methodology of six cultivars from the Colombian Caribbean region, with total carotenoid values ranging from 24.67 to 196.15 mg of β-carotene/100 g dry pulp; 84.30 to 161.49 mg Catequine eq./100 g dry pulp for the content of condensed tannins, and 91.80 to 259.23 mg/100 g dry pulp for mangiferin content. The ORAC methodology showed important antioxidant activity results, such as the Chancleta variety with the highest value (2163.78 μmol Trolox/100 g dry pulp). In conclusion, the evaluated mango varieties had promising results as functional food of high nutraceutical value, being Chancleta, Criollo and Jobo varieties, the fruits with highest content in bioactive compounds that expressed the best antioxidant activity.